Itch and Cough - Similar Role of Sensory Nerves in Their Pathogenesis - Pecova, T; Kocan, I; Vysehradsky, R; Pecova, R (Physiological research, 2020)
Itch is the most common chief complaint in patients visiting dermatology clinics and is analogous to cough and also sneeze of the lower and upper respiratory tract, all three of which are host actions trying to clear noxious stimuli. The pathomechanisms of these symptoms are not completely determined. The itch can originate from a variety of etiologies. Itch originates following the activation of peripheral sensory nerve endings following damage or exposure to inflammatory mediators. More than one sensory nerve subtype is thought to subservepruriceptive itch which includes both unmyelinated C-fibers and thinly myelinated Adelta nerve fibers. There are a lot of mediators capable of stimulating these afferent nerves leading to itch. Cough and itch pathways are mediated by small-diameter sensory fibers. These cough and itch sensory fibers release neuropeptides upon activation, which leads to inflammation of the nerves. The inflammation is involved in the development of chronic conditions of itch and cough. The aim of this review is to point out the role of sensory nerves in the pathogenesis of cough and itching. The common aspects of itch and cough could lead to new thoughts and perspectives in both fields.
Keywords: Nerve Fibers, Unmyelinated; nervová vlákna myelinizovaná; nervová vlákna nemyelinizovaná; Sensory Receptor Cells; lidé; agonisté histaminu; Histamine Agonists; Neurons, Afferent; pruritus; Cough; kapsaicin; Humans; látky ovlivňující senzorický systém; Sensory System Agents; Capsaicin; nervové receptory; zvířata; Pruritus; neurony aferentní; Animals; Nerve Fibers, Myelinated; Peripheral Nerves; periferní nervy; histamin; kašel; Histamine